ANALISIS HUKUM TERHADAP IMPLEMENTASI KRITERIA KETIDAKMAMPUAN FISIK DAN KESEHATAN SEBAGAI DASAR PERCERAIAN DI PENGADILAN AGAMA - Nurullah, Lutfi; Zeinudin, Moh.; Munir, Miftahul (JAS : Jurnal Ahwal Syakhshiyyah, 2023)
This research aims to uncover the basis of judges' considerations in deciding divorce cases due to physical disability or illness in one of the married couples and to understand the classification of physical disability or illness according to Law No. 1 of 1974 and Islamic law. The research method used is juridical-normative. The research findings indicate that in deciding divorce cases related to physical disability or illness, specifically in cases numbered 115/PDT.G/2005/PA.SMN and 209/PDT.G/2005/PA.SMN, the panel of judges at the Religious Court of Sumenep has followed the procedures stipulated in Articles 65 to 91 of Law No. 7 of 1989 and considered the provisions of Marriage Law and applicable regulations in Indonesia. The decisions are also supported by evidence presented by the litigants, in accordance with both Positive Law and Islamic Law. Moreover, the emphasis on applying Article 19 letter (e) of Government Regulation No. 9 of 1975 and Islamic Law is not solely on the criteria of physical disability or illness but is more focused on the inability to fulfill the obligations as a husband or wife. Therefore, divorce decisions must be supported by facts demonstrating the spouse's actual incapacity to fulfill their marital obligations. This is crucial to prevent the Judiciary from granting divorce too easily, in accordance with the principle stated in Article 39 of Law No. 1 of 1974, which aims to make divorce more challenging to obtain. Additionally, the saying of the Prophet Muhammad is mentioned, emphasizing that although divorce is permissible, it is highly disliked by Allah SWT.